2001
DOI: 10.1021/ja003180l
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Photochemical Reactivity in a Self-Assembled Monolayer on a Colloidal Gold Cluster

Abstract: A shell−core cluster 2 produced by depositing a self-assembled monolayer (SAM) of 6-thiohexyl-3-nitro-4-(4‘-stilbenoxymethyl)-benzoate (1) on a nanoparticulate gold colloid preserves normal solution-phase photoreactivity of the trans-stilbene and o-nitrobenzyl ether moieties, but shows quenched fluorescence. Nearest-neighbor aggregation is weaker for 1 bound to the roughly spherical colloidal gold particle (in cluster 2) than for analogous stilbenoids bound to a planar gold surface. Unlike the observed photoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 36 publications
1
110
0
Order By: Relevance
“…17 The emission wavelength of bound fluorophores on the metal particles was slightly shifted to 662 nm with a simultaneous band broadening, which was probably due to a restriction of movement for the bound fluorophore. 38 The hybridized DNA duplex chains can be regarded as the rigid rods that separate the fluorophores from the surfaces of metal cores. Since the DNA used in the current experiment contains 23 base pairs, the separation between the fluorophore and metal core is about 8 nm.…”
Section: Resultsmentioning
confidence: 99%
“…17 The emission wavelength of bound fluorophores on the metal particles was slightly shifted to 662 nm with a simultaneous band broadening, which was probably due to a restriction of movement for the bound fluorophore. 38 The hybridized DNA duplex chains can be regarded as the rigid rods that separate the fluorophores from the surfaces of metal cores. Since the DNA used in the current experiment contains 23 base pairs, the separation between the fluorophore and metal core is about 8 nm.…”
Section: Resultsmentioning
confidence: 99%
“…First, direct electronic coupling of a nanoparticle core with a chromophore due to proximity (55) might result in the complete quenching of the photoreaction, and second, steric constraints, which limit the conformational freedom of the molecular entities immobilized, affect photochemistry to varying degrees depending on the system. For example, the trans-cis isomerization of azobenzenes and stilbenes, chemisorbed on gold nanoparticles via a range of alkylthiol linker chain lengths, has been described (58,59). In these studies a clear dependence of photochemical quantum yield on chain length was observed, which was assigned to a distance-dependent quenching of the excited state through electronic coupling with the metal nanoparticle.…”
Section: Photoswitchable Molecularly Modified Nanoparticlesmentioning
confidence: 99%
“…Trans-cis isomerization of azobenzenes, [17][18][19] stilbenes [20] and overcrowded alkenes [21] chemisorbed on gold nanoparticles via alkylthiol linkers with a range of chain lengths have been reported. In these studies the effect of immobilisation on photochemical properties was of considerable interest both from molecule-surface and molecule-molecule interactions.…”
Section: Light Switching Of Molecules On Metallic Surfacesmentioning
confidence: 99%